The Effects of Forward Guidance: Theory with Measured Expectations - Mirko Wiederholt; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We study the effects of forward guidance with an approach that combines theory with experimental estimates of counterfactual expectation adjustments. Guided by the model, we conduct experiments with representative samples of the US population to study how households adjust their expectations in response to changes in the Fed's projections about future interest rates. Respondents significantly downward-adjust their inflation expectations in response to learning about an increase in the Fed's projection about the federal funds rate three years in the future, and they expect inflation to respond most strongly immediately after the announcement. By contrast, respondents do not adjust their nominal income expectations. Our model-based estimates highlight a small average consumption response to forward guidance due to opposing effects from intertemporal substitution and changes in expected real income.
Keywords: D12; D14; D83; D84; E32; G11; 330; Expectation Formation; Information; Updating